Health Policy on the pages of Revista de Saúde Pública - Aylene Bousquat; Oswaldo Yoshimi Tanaka
ABSTRACT We carried out a narrative review of the scientific production in the area of Policy, Planning and Management in Revista de Saúde Pública (RSP), between 1967 and 2015. All the fascicles of RSP, in the period, were accessed via SciELO platform, which provides all articles online. We selected and classified the articles according to the main topics of scientific production in the area of Policy, Planning and Management. Revista de Saúde Pública has published 343 articles on this subject, with significant growth in the last two decades. The most discussed topics were Health Economics, Primary Health-care, Access and Use of Health Services, and Evaluation of Services and Programs. In the last decade, the topics of Policy and Access to Medicines and Public-Private Relationship, including judicialization, gained importance. The pages of RSP embraced the vast and diverse production of Policy, Planning and Management in its first 50 years, contributing to the consolidation of the area in Brazil.